2018
DOI: 10.1002/eap.1782
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between plant drought response, traits, and climate of origin for green roof plant selection

Abstract: The ideal species for green or vegetated roofs should have high water use after rainfall to maximize stormwater retention but also survive periods with low water availability in dry substrates. Shrubs have great potential for green roofs because they have higher rates of water use, and many species are also drought tolerant. However, not all shrub species will be suitable and there may be a trade-off between water use and drought tolerance. We conducted a glasshouse experiment to determine the possible trade-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 60 publications
2
13
2
Order By: Relevance
“…Further, when water use was adjusted for shoot dry mass, plants with greater SLA also showed greater water use. This is consistent with other studies that showed positive relationships between water use, shoot dry mass, and SLA (Mitchell et al 2008, Markesteijn and Poorter 2009, Farrell et al 2013b, Du et al 2018. For instance, Nagase and Dunnett (2012) showed that for 12 species (forbs, sedums, and grasses) commonly planted on extensive green roofs in England, plants with greater shoot dry mass were more efficient at retaining rainfall, with bigger plants retaining close to 80% of the stimulated high-intensity rainfall.…”
Section: Water Use Was Positively Related To Fast Aboveground Traitssupporting
confidence: 90%
See 2 more Smart Citations
“…Further, when water use was adjusted for shoot dry mass, plants with greater SLA also showed greater water use. This is consistent with other studies that showed positive relationships between water use, shoot dry mass, and SLA (Mitchell et al 2008, Markesteijn and Poorter 2009, Farrell et al 2013b, Du et al 2018. For instance, Nagase and Dunnett (2012) showed that for 12 species (forbs, sedums, and grasses) commonly planted on extensive green roofs in England, plants with greater shoot dry mass were more efficient at retaining rainfall, with bigger plants retaining close to 80% of the stimulated high-intensity rainfall.…”
Section: Water Use Was Positively Related To Fast Aboveground Traitssupporting
confidence: 90%
“…2013, Du et al. 2018), plants with high water use are more likely to survive on green roofs through drought‐avoidance strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased precipitation can increase LNC (Sandel et al, 2010), but most traits and FDis have no significant relationships with increased precipitation in grasslands (Kimball et al, 2016;Xu et al, 2018). For desert shrub or shrub-dominated communities, increased precipitation can increase SLA of shrubs (Xin et al, 2018), but most traits are not related to experimental drought (Carvajal et al, 2017;Du et al, 2018). Furthermore, the available studies have documented inconsistent results on plant community trait responses to precipitation in geographic and experimental variations (Luo et al, 2018;Sandel et al, 2010;Zuo et al, 2017), due to different adaption and response of species to rapid precipitation changes.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of rainwater retention by the green roof is also dependent on the dynamic changes of water consumption between two rainfall events [18], the period of dry days, and plant drought tolerance [51]. Water loss on green roofs was mainly driven by plant ET [52].…”
Section: Discussionmentioning
confidence: 99%